P.'s Correspondence (From "Mosses from an Old Manse") - Hawthorne, Nathaniel, 1804-1864 (Salt Lake City, UT : Project Gutenberg, 2005)
"P.'s Correspondence (From 'Mosses from an Old Manse')" by Nathaniel Hawthorne is a short story published in 1845. The tale appears in Hawthorne's collection *Mosses from an Old Manse*, a work known for its allegorical nature and exploration of humanity's darker aspects. Like other stories in the collection, this piece reflects Hawthorne's characteristic focus on the negative dimensions of human nature, written during his years at the Old Manse with a meaning the author himself later admitted he could no longer fully comprehend. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Mosses_from_an_Old_Manse
Release date is 2005-11-01
David Widger and Al Haines
Keywords: Short stories; New England -- Social life and customs -- Fiction